O Algoritmo BARCOR: Classificação de Cortiça para Rolhas Recorrendo a Quatro Atributos de Qualidade (Silva Lusitana, 2008)
t. The author proposes an analytical method named algorithm BARCOR that integrates TOPSIS ("Technique for Order Preference by Similarity to Ideal Solution"), regression, tree models and cluster analysis, to select the minimum number of attributes of cork quality to efficiently classify this material when used to the production of stoppers. When using attributes evenly weighted he shows that only the four attributes are sufficient. If unevenly weights of the attributes are used, this number can be reduced to three. He proposes two models with four and three attributes as explanatory variables to obtain expedite and preliminary classifications of the cork. He admits that the algorithm has potential to be applied in other similar situations.